Pengembangan Media Pembelajaran Komik Matematika (KOMKA) untuk Meningkatkan Kemampuan Numerasi Siswa Sekolah Dasar - Saraswati, Laras; Zaenal, Reza Muhamad; Yusritawati, Ita (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the validity and effectiveness of the mathematical comic learning medium (KOMKA) to improve the numeration ability of elementary school students especially on area & volume measurement materials. This type of research is Research and Development. The development model used is the ADDIE model developed by Dick and Carey, which has five stages: Analysis, Design, Development, Implementation, and Evaluate. The population in this development research is all students of SDN 2 Padarek in the 2023/2024 academic year. The sampling technique used in this development research is simple random sampling. The data analysis technique used in this study is a descriptive analysis technique to describe whether the digital comics developed by the study are valid and effective for use in class learning. Research results show that the KOMKA learning medium is valid for use in learning activities, derived from the validity results of media experts and material experts. The KOMKA learning medium is effective in improving students' numeration skills. This can be seen from the average test results of students' mathematical understanding ability after the application of the KOMKA learning medium was higher than before.